Entrepreneurship performance in the EU: To what extent do economic, social, and government conditions matter? - Luz, A. R. C.; Bento, P.; Paschoalotto, M. A. C.; Pereira, R. (Journal of International Entrepreneurship, 2024)
Entrepreneurship is widely recognized as a key driver of economic development. At the same time, entrepreneurship is also affected by the economic conditions of the regions where it evolves. In the literature, negative impacts on entrepreneurial performance have been linked to the 2008 financial crisis in the European Union (EU). However, not enough evidence has been provided to support this assertion. To fill this gap, we tested the relationship between economic, social, and government conditions and entrepreneurial performance. We did this for opportunity entrepreneurship (OPP), necessity entrepreneurship (NEC), and total entrepreneurial activity (TEA), for the period 2003–2018, which covers before, during, and after the financial crisis. We considered 21 EU countries and applied descriptive, correlation, and multiple linear regression analyses. Our results demonstrate that (a) there is a positive and significant correlation between NEC and OPP, GDP per capita and OPP, unemployment and TEA, gender ratio and age, gender ratio and education, education and TEA, population and NEC, government indicators and GDP per capita, and government expenditure and NEC, and a negative and significant correlation between GDP per capita and TEA and (b) economic and government conditions had a negative impact on TEA, in contrast to a positive and negative impact on NEC. Social conditions are mixed for TEA and NEC and positive for OPP. The effects on economic conditions were mixed for OPP. Therefore, our study impacts practitioners by demonstrating the factors that do or do not impact entrepreneurial activity in the EU. Additionally, our study expands upon previously analyzed factors that influence entrepreneurial performance, promoting value and originality in the area.